Comparison of autologous platelet-rich fibrin matrix and transplantation of autologous noncultured epidermal cell suspension in the treatment of chronic non healing ulcer: Randomized comparative study - Satyendra K Singh; Sri Rupa (Wolters Kluwer Medknow Publications, 2022)
Context: Chronic non-healing ulcer causes significant morbidity, high cost and reduced quality of life. Aims: To compare autologous platelet-rich fibrin matrix and transplantation of autologous non-cultured epidermal cell suspension in the treatment of chronic non-healing ulcers. Methods: The study was single-centre, prospective, randomised comparative study conducted in a tertiary care center in North India. Patients with chronic non-healing ulcer were included and randomly divided into two treatment groups- Group 1: Platelet-rich fibrin matrix (PRFM) procedure was done every 2 weeks with maximum three sittings and in Group 2: Transplantation of autologous noncultured epidermal cell suspension (NCES) procedure was done once. Follow-up was done every 2 weeks for 8 weeks then monthly for up to 5 months to evaluate the healing of the ulcer. The data were analysed by statistical package for social science (SPSS) trial version 22. To find out a significant difference in mean value between groups, the Chi-square test, student's t-test, and Mann-Whitney U test were used. Results: A total of 41 patients were included in the study. Complete healing of ulcers occurred in 89.5% of the patients in the PRFM group and 93.8% of the patients in the NCES group at the end of 5 months (P = 0.33). The mean duration of complete healing in PRFM was 1.7 months and in NCES was 2.13 months (P = 0.20). Conclusions: Both procedures were effective, and there was no significant difference between the two procedures.